Pengaturan Peran Notaris dan Metode Penyimpanan Minuta Akta Notariil Digital di Era Industri 4.0 - Adintya Devi, Tjokorda Istri Agung; Wijaya, I Made Marta; Ari Atu Dewi, Anak Agung Istri (Acta Comitas : Jurnal Hukum Kenotariatan, 2023)
The purposes of this research are to identify and deciphere the Notary’s obligations and responsibilities to maintain the party’s information and data that contained in the Minutes of Deed pursuant to Amandement Notary Position Act and to analyze and elaborate th further method of storing the Minutes of Deed digitally based on the applicable laws. This study is used normative legal research that combined with several approaches namely legal concept analysis and statutory approach, also this study used qualitative analysis techniques through with several steps, namely systematization, description, and explanation. The research finds out that the Notary’s obligations and responsibilities to maintain the party’s information and data that contained in the Minutes of Deed as regulated in Article 16 paragraph (1) letter b and letter f. The method for storing Minutes of Deed digitally in the future is in accordance with the provisions of GR Number 28 of 2012, the ITE Law, and the Amendment  Notary Position Act by Notaries to digitize the Minutes of Deed as part of the Notary Protocol is by transferring media as regulated in GR Number 28 of 2012 with stages, namely scanning or scanning of Minutes of Deed, authentication of digital Minutes of Deed, and storage of digital Minutes of Deed in physical storage media or cloud computing.